1989
DOI: 10.1073/pnas.86.19.7616
|View full text |Cite
|
Sign up to set email alerts
|

Transformation of siphon responses during conditioning of Aplysia suggests a model of primitive stimulus-response association.

Abstract: A semi-intact preparation was used to study the effects ofclassical conditioning on the type ofsiphon response elicited by a conditioned stimulus to the mantle ofAplysia. Five pairings of the conditioned stimulus with an unconditioned stimulus to nerves from the tail transformed the constricting alpha response of the siphon into a conditioned flaring response resembling the unconditioned response to stimulation of the tail nerves. Although some pseudoconditioning occurred, an associative component was indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 35 publications
1
14
0
Order By: Relevance
“…First, they extend the findings of other studies showing that Aplysia was able to detect and learn about different chemosensory and tactile stimuli Carew et al, 1981;Colwill et a!., 1988;Walters et al, 1981). Second, they confirm previous reports documenting that Aplysia was sensitive to the temporal arrangements ofCSs and USs (Hawkins, Carew, & Kandel, 1986;Hawkins, Lalevic, Clark, & Kandel, 1989;Walters, 1989). It is especially impressive that responding was greater to the CS+ than to the CS -in each of the experiments reported here independently of the specific stimulus identities.…”
Section: Discussionsupporting
confidence: 80%
“…First, they extend the findings of other studies showing that Aplysia was able to detect and learn about different chemosensory and tactile stimuli Carew et al, 1981;Colwill et a!., 1988;Walters et al, 1981). Second, they confirm previous reports documenting that Aplysia was sensitive to the temporal arrangements ofCSs and USs (Hawkins, Carew, & Kandel, 1986;Hawkins, Lalevic, Clark, & Kandel, 1989;Walters, 1989). It is especially impressive that responding was greater to the CS+ than to the CS -in each of the experiments reported here independently of the specific stimulus identities.…”
Section: Discussionsupporting
confidence: 80%
“…Behavioral conditioning in this preparation is similar to conditioning of siphon withdrawal in intact Aplysia (Carew et al, 1981) and conditioning of gill withdrawal in another simplified preparation , both of which display additional higher-order features that are characteristic of conditioning in vertebrates Hawkins et al, 1986Hawkins et al, , 1998Colwill et al, 1988a,b;Walters, 1989). With the siphon withdrawal preparation, it is relatively easy to examine behavioral conditioning while simultaneously monitoring PSPs between identified sensory and motor neurons that contribute to the behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Conditioning of the withdrawal reflex has many of the behavioral features characteristic of conditioning in mammals, including stimulus specificity , response specificity Walters, 1989), temporal specificity and effects of contingency (Hawkins et al, 1986), as well as several effects of context (Colwill et al, 1988a,b) and both forward and simultaneous second-order conditioning . These behavioral results suggest that conditioning in Aplysia and in mammals may share common cellular and molecular mechanisms.…”
Section: Abstract: Aplysia; Classical Conditioning; Synaptic Plasticmentioning
confidence: 99%
“…First, a number of studies have shown that the topography of the CR depends upon the identity of the US Hawkins, Lalevic, Clark, & Kandel, 1989;Jenkins & Moore, 1973;LaMon & Zeigler, 1984;Skelton, Spetch, & Wilkie, 1980;Spetch, Wilkie, & Skelton, 1981;Walters, 1989). In a classic study of autoshaping, Jenkins and Moore (1973) observed that the response to the CS captured features characteristic of the response to the US paired with that CS.…”
Section: Discussionmentioning
confidence: 99%